2000
DOI: 10.1212/wnl.54.2.412
|View full text |Cite
|
Sign up to set email alerts
|

APOE ε4 does not predict mortality, cognitive decline, or dementia in the oldest old

Abstract: The lack of association between APOE epsilon 4 carrier status and mortality, or development of dementia, or cognitive decline in these very elderly people, whether analyzed in the whole population or among the nondemented subjects only, suggests that the APOE epsilon 4 effect in younger subjects is age-dependent, and that it is no longer present in very old age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
2
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 21 publications
11
71
2
1
Order By: Relevance
“…Consistent with our results, most studies have shown a strong relationship between APOE4ϩ status and dementia incidence in participants with cognitive impairment, 30 -32 but not all studies have found the relationship. 33,34 We found memory impairment to be an important factor leading to higher rates of incident dementia, particularly AD. Participants with aMCI progressed to dementia at a high rate of 31% per year, whereas participants with OCI progressed to dementia at nearly 40% per year.…”
Section: Resultsmentioning
confidence: 86%
“…Consistent with our results, most studies have shown a strong relationship between APOE4ϩ status and dementia incidence in participants with cognitive impairment, 30 -32 but not all studies have found the relationship. 33,34 We found memory impairment to be an important factor leading to higher rates of incident dementia, particularly AD. Participants with aMCI progressed to dementia at a high rate of 31% per year, whereas participants with OCI progressed to dementia at nearly 40% per year.…”
Section: Resultsmentioning
confidence: 86%
“…Although the association of APOE e4 with incident MCI has not been reported in the oldest old, the impact of the e4 allele on dementia risk is thought to be minimal or absent in the oldest old. 32 In the 901 study, APOE e4 carrier status (vs e3e3) was associated with dementia in cross-sectional but not in prospective analyses. 33 The frequency of an APOE e4 allele was only 8.1% in the incident cohort, compared to 18.8% in the present study.…”
Section: -19mentioning
confidence: 93%
“…Studies that found a positive correlation between severity of dementia and mortality were not exclusively based on an observation interval of more than 5 years. Yet, two studies had a shorter period of observation [25,32] and neither of them showed a signifi cant correlation between severity of the disorder and mortality risk. Aevarsson et al [20] observed that patients with a mild AD tended to have a higher mortality only at the end of a 7-year observation interval.…”
Section: Specifi C Characteristics Of the Disordersmentioning
confidence: 99%